(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
This article is devoted to the Sobel algorithm implementation for detection an object contour in the mobile robot’s workspace in real time. Mathematical models of the algorithm functioning were examined in detail, and the developed program in Python in the PyCharm environment was subjected to a series of experiments. The experimental results indicate the outstanding performance of the algorithm, reaching 30.00 frames per second when processing a video stream. However, the contouring speed of 1.19 frames per second indicates potential performance challenges when working in dark conditions using artificial side lighting. The research results presented in the article highlight the effectiveness of the algorithm in real-time conditions and highlight the importance of taking into account lighting features when using it in mobile robots.